Protective Effect of Morus nigra L. (Mulberry) Fruit Extract on the Liver Fatty Acid Profile of Wistar Rats - Aydin, Sevinc; Yilmaz, Okkes; Gokce, Zehra (Zoological Soc Pakistan, 2015)
Antioxidants are not only produced by the body cells but can also be obtained through food. As is known, fruits and vegetables contain molecules which have antioxidant activities. These molecules protect tissues against stress and diseases. In this study, it was aimed to investigate the protective effect of the methanol extract of Morus nigra L. fruit on the prevention of lipid peroxidation (LPO) by analyzing lipid fraction of liver tissue and fatty acid profiles of Wistar rats by using Gas chromatography. Statistically no significant difference was observed in the hepatic lipid fractions of rats containing M. nigra fruit extract and the control group. However, the level of LPO were found to be very high in the group which contained Fenton reagent compared to the groups that contained M nigra and antioxidant molecules (p < 0.001). Besides that, it was found that saturated and unsaturated fatty acid levels were higher in the groups including resveratrol and fruit extract compared to the group including Fenton reagent (p < 0.001). We believe that the main reason for the decrease in the amount of LPO and the protection of fatty acids is the presence of antioxidant molecules in the fruit.
Keywords: Morus nigra L.; black mulberry; lipid peroxidation; fatty acids; Fenton reagent (Fenton R, H2O2 + FeCl2)